Fermentation Kinetics of Gluten-Free Breads: The Effect of Carob Fraction and Water Content - Kleopatra Tsatsaragkou; Ioanna Mandala; Nikolaos G. Stoforos (Foods, 2023)
In this study, gluten-free doughs with rice flour, substituted by 15% fractions of different carob seed flours, were prepared by varying their water content. The coarse carob fraction A (median particle size of flour, D50: 258.55 μm) was rich in fibers, fraction B (D50: 174.73 μm) was rich in protein, C (D50: 126.37 μm) was rich in germ protein, and fraction D (D50: 80.36 μm) was a mix, reconstituted from the other fractions and pulverized using a jet mill. Τhe experimental data of the dough’s volume over time were fitted to the Gompertz model for each carob fraction and water content. The calculated parameters of the model were the maximum relative volume expansion ratio (a), the maximum specific volume growth rate (μ), and the time lag of the leavening process (tlag). Gompertz’s equation adequately described the individual experimental curves. In the next step, a composite model was applied for each carob fraction where the parameters a and tlag were expressed as quadratic functions of water content levels (W), while μ was linearly dependent on W. Each carob fraction presented an optimum water content level for which dough height was maximized and time lag was minimized. Optimized dough volume could be predicted by the composite model; it was shifted to lower values as finer carob flour was used. In respect to baked products, softer breads were produced using finer carob flour and porosity values were higher at optimum water content levels. The investigated fermentation kinetics’ models provide significant information about the role of water and carob flour on gluten-free dough development and bread volume expansion.